2018
DOI: 10.1080/14767058.2018.1484092
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal condition is associated with adverse perinatal outcomes and premature rupture of membranes in low-income pregnant women in Bogota, Colombia: a case–control study

Abstract: Periodontal condition is a factor independent of other important risk factors for a perinatal adverse outcome and PRM. Prevention of periodontal disease should be included in preconception and prenatal care programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
15
0
3
Order By: Relevance
“…Table 2 shows that the average gestation age of mature infants at the time of birth was 38.5 ± 0.2 weeks, of premature infants with low body weight (LBW)-32.4 ± 1.3 weeks, of very low body weight (VLBW)-28.8 ± 0.6 weeks, and of extremely low body weight (ELBW)-27 ± 0.0 weeks. At the same time, changes in the average body weight in mature newborns remained in the range of 3.000 ± 117 g, in premature infants with LBW-1.927.3 ± 239.5 g, with VLBW-1.309.6 ± 128.6, and with ELBW-920 ± 55.2 g [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 shows that the average gestation age of mature infants at the time of birth was 38.5 ± 0.2 weeks, of premature infants with low body weight (LBW)-32.4 ± 1.3 weeks, of very low body weight (VLBW)-28.8 ± 0.6 weeks, and of extremely low body weight (ELBW)-27 ± 0.0 weeks. At the same time, changes in the average body weight in mature newborns remained in the range of 3.000 ± 117 g, in premature infants with LBW-1.927.3 ± 239.5 g, with VLBW-1.309.6 ± 128.6, and with ELBW-920 ± 55.2 g [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the results of our study, some studies have reported a significant association between dental decays and preterm labor. In a study conducted by Mattheus et al on 4309 pregnant women during 2009-2011, the results revealed that one in five women received dental services during pregnancy and the incidence of preterm labor was higher in these women (30). In a case-control study on 111 pregnant women, Márquez-Corona et al in 2019 found a significant relationship between the rate of preterm labor and the severity of dental disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al, in a large cohort study and a smaller case–control study, did not find any correlation between preterm birth and periodontal disease [ 62 , 63 ]. Lafaurie et al, in a case–control study, concluded that the presence of periodontal pockets was not a risk factor for preeclampsia, but they reported an association between periodontal pockets and premature rupture of membranes, low birth weight, and preterm birth [ 64 ].…”
Section: Discussionmentioning
confidence: 99%